The impact of pedestrian countdown signals on pedestrian–motor vehicle collisions: a quasi-experimental study. Issue 4 (10th December 2011) - Camden, Andi; Buliung, Ron; Rothman, Linda; Macarthur, Colin; Howard, Andrew
Abstract : Objective: To determine whether pedestrian countdown signals (PCS) reduce pedestrian–motor vehicle collisions in the city of Toronto, Canada. Methods: A quasi-experimental study design was used to evaluate the effect of PCS on the number of pedestrian–motor vehicle collisions in the city of Toronto, from January 2000 to December 2009. Each intersection acted as its own control. We compared the number of pedestrian–motor vehicle collisions per intersection-month before and after the intervention. Stratified models were used to evaluate effect modification by pedestrian age, injury severity and location (urban vs inner suburbs). Poisson regression analysis with repeated measures (generalised estimating equations) was used to estimate the RR and 95% CI. Results: The analysis included 9262 pedestrian–motor vehicle collisions at 1965 intersections. The RR of collisions after PCS installation was 1.014 (95% CI 0.958 to 1.073), indicating no statistically significant effect of PCS on collisions. There was no evidence to suggest effect modification between PCS and collisions by age, injury severity or location. Conclusion: The installation of PCS at 1965 signalised intersections in Toronto did not reduce the number of pedestrian–motor vehicle collisions at these intersections.